Chromosome divergence and NOR polymorphism in Bryconamericus aff. iheringii (Teleostei, Characidae) in the hydrographic systems of the Paranapanema and Ivaí Rivers, Paraná, Brazil - Thiago Gomes Capistano; Ana Luiza de Brito Portela Castro; Horácio Ferreira Julio-Junior (Genetics and Molecular Biology, 2008)
Cytogenetic studies were carried out in three populations of Bryconamericus aff. iheringii from two hydrographic systems of the Paranapanema and Ivaí Rivers, separated by a watershed, both belonging to the upper Paraná River basin. Specimens had a constant diploid number 2n = 52 chromosomes. However, three karyotype formulae were identified in the three populations: B. aff. iheringii from the Maringá stream had 12M+18SM+8ST+14A (FN = 90); specimens from Keller River showed 8M+28SM+6ST+10A (FN = 94) and specimens from the Tatupeba stream had 8M+20SM+8ST+16A (FN = 88). Nucleolar organizer regions (NORs) were identified by silver nitrate staining and fluorescent in situ hybridization (FISH) with an 18S rDNA probe. Specimens from Tatupeba stream had a simple NOR system located in a terminal position of the short arm of a pair of large submetacentric chromosomes. Ag-NOR and FISH methodologies revealed multiple NORs in specimens of the Maringá stream and Keller River. Differences in chromosome structure and in NOR patterns in the three populations of B. aff. iheringii revealed fixed evolutionary chromosome divergence. Aspects related to karyotypic variations and to geographic isolation of these populations are discussed.